Does CSR increase cost stickiness? - Ika Kristianti; Etna Nur Afri Yuyetta (University of Merdeka Malang, 2022)
This study aims to provide evidence of corporate social responsibility (CSR) engagement with cost stickiness. Cost stickiness is an asymmetrical cost behavior in which the magnitude of the increase in costs tends to be higher when there is an increase in activity compared to the decrease in costs when there is a decrease in activity. The pattern of changes in costs depends not only on the size of the activity but also on the direction of the change. The research hypothesis states that the involvement of CSR requires the long-term commitment of the company in value creation activities, so it is difficult to suppress committed resources instantly. This study uses employee welfare costs and donations as a proxy for CSR. The research sample is a manufacturing company in Indonesia, with the observation year of 2017–2020. The results of the study prove that there is cost stickiness in selling, administrative, and general costs, and the degree of cost stickiness increases when CSR costs are added to the research model. The results also confirm that changes in activity levels and changes in costs are not always the same. These findings provide new evidence for understanding how CSR affects cost stickiness in manufacturing firms.